(untitled) (Research, Society and Development, 2021)
Objective: To determine the pathogens that most cause infection in burn patients and quantify their frequency. Methodology: An integrative literature review of articles published from 2016 to 2021, available in the databases LILACS, PubMed and SciELO, 18 articles were included in this study. Results: The frequency of gram-positive bacteria ranged from 21,8 to 24%, while gram-negative 70,3-78%. The wound cultures revealed Pseudomonas (14,3-45,2%), Staphylococcus (0-43,9%), Acinetobacter (3,6-52,8%), Proteus (0-16%), Enterobacter (0-12,1%), Klebsiella (0-28%) and E. coli. (0-8,5%). The general cultures tissues showed Pseudomonas (17-49,9%), Staphylococcus (6.5-31.2%), Coagulase Negative Staphylococcus (CoNS) (0-22%), Acinetobacter (0-16,7%), Proteus (0-0,9%), Enterobacter (0-37%), Klebsiella (0-14,3%), Enterococci (0-2,8%) and Serratia (0-1,2%). Final Considerations: The detected agents of infection suffered several frequency variations in our analysis. The knowledge about these germs is essential for the correct management and reduction of the mortality rate in burn patients This kind of study must be carried out periodically, with the purpose of information does not lag over time.